A psycholinguistics view on a child’s speech production in babbling stage: A case study - Puput Jianggimahastu Larastika Suryanto; Rizqi Husaini (Journal of English Language Teaching and Learning (JETLE), 2023)
This study aims to examine a baby's babbling child's speech production seen from psycholinguistics view. It also aims to reveal the phonological organization, contextualize meaning, and decipher meaning of the baby’s babbling stage. The participant was an infant who was at the stage of babbling at eight months old. This study used case study as the research design. Moreover, the data was collected by using direct observation, document and parents’ interview. The results shows that there were 99 patterns in the baby’s babbling stage. Furthermore, the babbling topic occurred in several contexts, with each babbling having a varied meaning depending on the situation.